Effectiveness of an intervention with mothers to stimulate children under two years - Isolda Maria Barros Torquato; Neusa Collet; Franklin Delano Soares Forte; Jael Rúbia Figueiredo de Sá França; Maria de Fátima de Oliveira Coutinho Silva; Altamira Pereira da Silva Reichert (Universidade de São Paulo, 2019)
Objective: To analyze the effectiveness of an educational intervention with mothers to stimulate children under two years of age at risk for neuropsychomotor development. Method: Before-after intervention study, conducted with 52 mothers of children under two years old, enrolled in reference centers in early childhood education. Initially, maternal knowledge regarding child development and stimulation was assessed through a structured instrument. Then, workshops were held with the mothers and, after three months, maternal knowledge was revised, reapplying the data collection instrument. In the analysis, descriptive and inferential statistics were used, applying the McNemar and Wilcoxon tests and the Rasch Model from the Item Response Theory. Results: after the intervention, there was a significant increase in scores regarding the following aspects: knowledge of mothers about child development and stimulation from 5.77 ± 1.85 to 18.60 ± 1.94 (p <0.001); reduction of the maternal difficulty index in answering the instrument questions from 1.17 ± 0.57 to -1.98 ± 1.63 (p 0.01). Conclusion: the educational intervention contributed to the improvement of maternal knowledge regarding the development and forms of child stimulation, corroborating the importance of this action to advance the health of children at risk under maternal care at home.